A simulation model of Gerotor pumps considering fluid–structure interaction effects: Formulation and validation. (June 2020) - Pellegri, Matteo; Manne, Venkata Harish Babu; Vacca, Andrea
Highlights: The proposed simulation model evaluates different flow, force features of a Gerotor. The model considers different fluid–structure interactions of the rotors. Flow rate, pressure pulsation and mechanical efficiency are experimentally validated. Torque losses are quantified, considering possible asymmetry of the axial gap. Abstract: Gerotors are compact, inexpensive and robust pumps generally used in hydraulic systems. Owing to their characteristic operation at low pressure (up to 30 bar), these units can be modelled using relatively simple tools considering only their fluid dynamics aspects. However, some commercially available Gerotors operate at higher pressures so that material deformation effects cannot be neglected under such conditions. This paper presents an omni-comprehensive simulation approach for Gerotor units that considers the fluid–structure interaction effects at the lateral lubricating gaps and related to the contacts between the rotors. The numerical tool consists of different submodels which allow the evaluation of the fluid dynamic features of the flow through the pump considering micro-motion effects of the rotors. This paper particularly details the novel aspects of the simulation approach, which is the introduction of submodels that account for fluid–structure interaction effects: the lateral lubricating gap models and the rotor contact models, both based on the solution of the Reynolds equation considering the deformation of the solid parts. For the model validation, a commercially available pump able to operate above 100 bar was tested at the authors' research center. The comparison between the simulation results and the experimental data clearly show the good accuracy of the model, in terms of volumetric flow and port pressure pulsation. In particular, the model allows predicting both the volumetric and the torque efficiency of the unit. Furthermore, the simulation results permit to interpret the reasons for instances of wear present in the unit.